The effectiveness of a therapeutic parenting program for children aged 6–11 years with behavioral or emotional difficulties: Results from a randomized controlled trial. (October 2020) - Axford, Nick; Bjornstad, Gretchen; Matthews, Justin; Heilmann, Sarah; Raja, Anam; Ukoumunne, Obioha C.; Berry, Vashti; Wilkinson, Tom; Timmons, Luke; Hobbs, Tim; Eames, Tim; Kallitsoglou, Angeliki; et al.
Highlights: The intervention was not more effective than services as usual at improving outcomes. This may relate, in part, to implementation issues; fidelity could be improved. It may also reflect the relative lack of behavioral components in the program. Abstract: Objective: The aim of the study was to evaluate the implementation and effectiveness of a therapeutic parenting program that targets parents of children aged 6 to 11 years identified as having behavioral and emotional difficulties. The intervention comprises two parts, delivered sequentially: a 10–12-week group-based program for all parents, and one-to-one sessions for up to 12 weeks with selected parents from the group-based element. Methods/Design: In a randomized controlled trial, 264 participants were allocated to the Inspiring Futures program (intervention) or services as usual (control) arms with follow-up assessments at 16 (post-group program) and 32 (post-one-to-one sessions) weeks. The primary outcome was the parent-rated Strengths and Difficulties Questionnaire (SDQ) Total Difficulties score at 32 weeks. Secondary outcomes included parent-rated SDQ subscales, parent coping strategies, empathy in parenting and parenting skills. Results: All 264 participants were included in outcome analyses. There was no statistically significant effect on SDQ Total Difficulties (standardized mean difference: −0.07; 95% CI: −0.30 to 0.16; p = 0.54). There were no sub-group effects. Only 1 of 40 comparisons between the trial arms for secondary outcomes across both follow-ups was statistically significant at the 5% level. The mean number of group sessions attended by intervention arm participants was 6.1 (out of 10 to 12) and only 1 in 20 intervention arm participants received one-to-one support. Independent observation indicated scope to improve fidelity in terms of adherence, quality and participant responsiveness. Conclusions: The intervention is not more effective than services as usual at improving targeted outcomes. This may be related, in part, to implementation issues but arguably more to the inability of a non-behavioral intervention to improve caregiving adequately, particularly when it is not targeted at new parents who have experienced trauma or deprivation early in life or subsequently.